ACE2 (Angiotensin-Converting Enzyme 2) in Cardiopulmonary Diseases: Ramifications for the Control of SARS-CoV-2. Issue 3 (September 2020) - Sharma, Ravindra K.; Stevens, Bruce R.; Obukhov, Alexander G.; Grant, Maria B.; Oudit, Gavin Y.; Li, Qiuhong; Richards, Elaine M.; Pepine, Carl J.; Raizada, Mohan K.
Abstract : Discovery of ACE2 (angiotensin-converting enzyme 2) revealed that the renin-angiotensin system has 2 counterbalancing arms. ACE2 is a major player in the protective arm, highly expressed in lungs and gut with the ability to mitigate cardiopulmonary diseases such as inflammatory lung disease. ACE2 also exhibits activities involving gut microbiome, nutrition, and as a chaperone stabilizing the neutral amino acid transporter, B 0 AT1, in gut. But the current interest in ACE2 arises because it is the cell surface receptor for the novel coronavirus, severe acute respiratory syndrome coronavirus-2, to infect host cells, similar to severe acute respiratory syndrome coronavirus-2. This suggests that ACE2 be considered harmful, however, because of its important other roles, it is paradoxically a potential therapeutic target for cardiopulmonary diseases, including coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2. This review describes the discovery of ACE2, its physiological functions, and its place in the renin-angiotensin system. It illustrates new analyses of the structure of ACE2 that provides better understanding of its actions particularly in lung and gut, shedding of ACE2 by ADAM17 (a disintegrin and metallopeptidase domain 17 protein), and role of TMPRSS2 (transmembrane serine proteases 2) in severe acute respiratory syndrome coronavirus-2 entry into host cells. Cardiopulmonary diseases are associated with decreased ACE2 activity and the mitigation by increasing ACE2 activity along with its therapeutic relevance are addressed. Finally, the potential use of ACE2 as a treatment target in COVID-19, despite its role to allow viral entry into host cells, is suggested.